Radical Neorealism in Postwar Italian Cinema : Rethinking Cesare Zavattini’s Poetics of Objectivity - Borjan, Etami (2012)
The aim of the article is to discuss the concept of Neorealism in the works of Cesare Zavattini, one of the most prominent postwar Italian screenwriters and film critics. He was credited as “the father of Neorealism” despite the fact that his ideas on cinema differed in many aspects from the well-known Neorealist poetics. Film-pedinamento, film lampo, film inchiesta, are some of the terms used by Zavattini. The new Neorealist cinema, argued Zavattini, goes far beyond traditional classifications such as film genres. Cinema in its ontological objectivity was seen as reality captured without any intrusion. Cinema should coincide with the reality but shouldn’t be a pure mimesis of it. It is not so important to represent the reality but to comprehend it. Throughout his career Zavattini argued that cinema should be socially committed art. In order to obtain that goal it should undergo a process of “democratization” and become accessible to the masses. In order to understand Zavattini’s radicalism it is necessary to contextualize his assumptions within the historical frame of the postwar Italian film criticism, and to juxtapose them with the current debates on Neorealism. The article highlights the controversies of Zavattini’s poetics of Neorealism by re-evaluating it in relation to semiotic texts on (neo)realist theories (Deleuze, Eco, Winston, Bettetini, Stam) and to some recently published debates on the postwar Italian cinema (Cardullo, Nowell-Smith, Spinelli Coleman, and others).
Projekt MZOS
ENG